The magazine aonde vamos? Publishes the khrushchev report - Chermont, Lucia [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2021)
The magazine Aonde Vamos? (1943-1977), a weekly Rio de Janeiro publication by the Jewish community, with a strong critical and ideological bias, linked to the Zionist right, emerged during a period of great transformations, such as the integration and affirmation of this group in the face of the tragic legacy of the Holocaust and the tense expectations arising from the recent foundation of the State of Israel. This article analyzes the pioneering and full publication of the Kruschev report by the magazine Aonde Vamos? between June 21 and July 19, 1956. The report had been presented at the 20th Congress of the Communist Party of the Soviet Union on February 14 of the same year and exposed abuses of the Soviet Stalinist period. This article aims to shed light on how the circulation of ideas and information was intense and had a transnational character, in addition to highlighting how these ideas and information were loaded with meanings and representations for certain ideological lines of the Jewish community. Based on a theoretical-methodological contribution of Cultural History and Representations, we sought to understand the uses and representations of the document by the Brazilian Jewish press, as well as its position regarding the report and the meaning and value of its publication in the magazine Aonde Vamos?.
A revista aonde vamos? Publica o relatório kruschev
Keywords: Contemporary history; Jewish press in brazil; Transnational history